Ultrasound evaluation of fetal central nervous system anomalies and its correlation with postnatal outcome - Navkiran Kaur; Amanjeet Kaur; Saryu Gupta; Parneet Kaur; Jaswinder Kaur Mohi; Manjit Singh Guliani (International Journal of Medical Research and Review, 2017)
Introduction: CNS anomalies are the most serious congenital abnormalities. Ultrasound is an effective and non invasive modality of prenatal diagnosis of these anomalies. The purpose of the current study was to determine the frequency of CNS anomalies and its postnatal outcome.Objectives: Present study was undertaken to find out the incidence of CNS anomalies in utero by ultrasound and to confirm them by autopsy or postnatal examination.Materials and Methods: Ultrasound scanning of 5761 pregnant women was performed. Pregnancies with ultrasound findings of CNS anomalies were followed up. Prenatal findings were compared with postnatal findings and confirmed by autopsy wherever possible. In case of live birth post natal findings were noted.Results: Ultrasound detected 50 anomalies in 42 cases. Ultrasound findings were exactly matching in 90%. 4 cases had variations 3 on autopsy & 1 on postnatal USG.Conclusion: The incidence of CNS malformations on ultrasound was 0.73%. Autopsy and postnatal findings showed high degree of correlation with prenatal ultrasound findings.